Numerical investigation of phase change materials thermal capacitor for pipe flow - Kurnia, J.C. (EDP Sciences, 2017)
This study addresses the performance of phase change material as thermal capacitor. A computational fluid dynamics (CFD) model is developed to take into account the conjugate heat transfer between water as the heat transfer fluid (HTF) and PCM as thermal capacitor. A pulsating inlet temperature with constant inlet velocity is prescribed to represent temperature variation. The performance of thermal capacitor is evaluated by closely monitoring outlet temperature and comparing it with inlet temperature to examine the reduction in temperature fluctuation. To intensify heat transfer between HTF and PCM, extended surfaces (fins) are installed on PCM side. The results indicate that PCM thermal capacitor can reduce temperature fluctuation by ∼ 1 °C. This reduction can be improved further when extended surface is installed with ∼ 1.5 °C reduction in temperature fluctuation is achieved. Moreover, it is found that the maximum temperature is delayed at the outlet due to slow conjugate heat transfer between HTF and PCM. Inlet velocity is found to have considerable influence of the temperature fluctuation reduction: Slower inlet velocity results in a better temperature fluctuation reduction. This study is expected to serve as a guideline in designing PCM-based thermal capacitor. © The authors, published by EDP Sciences, 2017.